TINJAUAN TEORITIS BIAYA LINGKUNGAN TERHADAP KUALITAS PRODUK DAN KONSEKUENSINYA TERHADAP KEUNGGULAN KOMPETITIF PERUSAHAAN - GUNAWAN, ERIC (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
Environmental costs is a way to calculate the costs to the environment, including reporting, and reduce environmental impact. Applicable environmental costs aimed at reducing the negative impact on the environment by considering the company's environmental problems in every business decision and the company's production process. By applying the company's environmental costs are expected to reduce negative impacts on the environment arising from corporate activities. One way to identify various sources of waste and waste that cause inefficient production so that the environmental information that helps management in making or decision-making according to the researchers considered the application of environmental costs can provide huge profits for companies, especially in the financial aspects of this led management are motivated to reduce the environmental costs or reduce these costs. In this papers will be discussed how the application of environmental impact and costs of implementing the company incurred to implement the environmental costs that can affect product quality and company create a competitive advantage.